PENERAPAN PENDEKATAN REALISTIK MATEMATIS UNTUK MENINGKATKAN HASIL BELAJAR HIMPUNAN SISWA KELAS VII SMP PGRI ARJASARI - Desi Aryanti Hidayat; Asep Ikin Sugandi; Artika Artika (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2021)
This research is a classroom action research. The problem formulated in this study is whether through a mathematical realistic approach can improve the results of junior high school students' results on set material? The aim is to examine increasing mastery of set concepts. This research was conducted on students of class VII-C SMP PGRI Arjasari 2019/2020 school year with a total of 36 students. The instrument used was a test of learning outcomes as a test of students' mastery of mathematical concepts, for initial tests (before action), cycle I tests and II (after giving the action), and observation sheet at the time of giving and implementing the action. The results of the analysis obtained based on written tests carried out there was an increase in the average learning outcomes In the second cycle, the first meeting average value of 70.1 with the highest value of 90 and the lowest value of 45. After carrying out the actions in the second cycle of the second meeting there was an increase in the results student learning. This is seen in the average value of 80.92 with the highest value of 100 and the lowest value of 50. The percentage of classical completeness increased from the first cycle of meeting 1 by 25% and meeting 2 by 38%. Furthermore, in the second cycle also increased, at the first meeting 69% to 86%. Means that had reached more than or equal to the specified KKM 70. At the end of the first cycle student learning outcomes seen that at the end of the first cycle the percentage of learning completeness was 38% and does not meet the classical learning completeness criteria that have been determined, then the research is continued to the second cycle. After the implementation of the second cycle, shows that at the end of the second cycle learning achievement reached 86% with the number of students who completed as many as 31 students, meaning completeness based on the number of students when that is 36 people, because there are 5 people who haven't finished.